Monoclonal antibodies as probes of tetanus toxin structure and function. - Kenimer, J G (1983)
Monoclonal antibodies specific for fragment B, fragment C, and light chain of tetanus toxin were prepared by fusion of P3X63Ag8 BALB/c myeloma cells with spleen cells from BALB/c mice immunized with tetanus toxoid or fragment B. Hybridoma colonies were assayed for antibody production by an enzyme-linked immunosorbent assay. Fourteen positive clones were identified, cloned by limiting dilution, and injected intraperitoneally into mice to obtain ascites fluids. Thirteen of the monoclonal antibodies were of the immunoglobulin G1 subclass and one was immunoglobulin G2. Two of the antibodies were directed against sites on fragment C, nine were directed against the light chain, and three were directed against the portion of fragment B which does not comprise the light chain of tetanus toxin. At least one antibody in each group exhibited significant toxin neutralization activity. However, only one of these neutralizing antibodies strongly inhibited the binding of 125I-tetanus toxin to ganglioside-coated plates. These data indicate that interference with receptor recognition is not the only means of neutralizing tetanus toxin. Monoclonal antitoxins as potential therapeutic and prophylactic reagents are discussed.